Genome-wide analysis of WRKY transcription factor genes in Toona sinensis: An insight into evolutionary characteristics and terpene synthesis - Ren, Liping; Wan, Wenyang; Yin, Dandan; Deng, Xianhui; Ma, Zongxin; Gao, Ting; Cao, Xiaohan (Frontiers in Plant Science, 2023)
WRKY transcription factors (TFs), one of the largest TF families, serve critical roles in the regulation of secondary metabolite production. However, little is known about the expression pattern of WRKY genes during the germination and maturation processes of Toona sinensis buds. In the present study, the new assembly of the T. sinensis genome was used for the identification of 78 TsWRKY genes, including gene structures, phylogenetic features, chromosomal locations, conserved protein domains, cis-regulatory elements, synteny, and expression profiles. Gene duplication analysis revealed that gene tandem and segmental duplication events drove the expansion of the TsWRKYs family, with the latter playing a key role in the creation of new TsWRKY genes. The synteny and evolutionary constraint analyses of the WRKY proteins among T. sinensis and several distinct species provided more detailed evidence of gene evolution for TsWRKYs. Besides, the expression patterns and co-expression network analysis show TsWRKYs may multi-genes co-participate in regulating terpenoid biosynthesis. The findings revealed that TsWRKYs potentially play a regulatory role in secondary metabolite synthesis, forming the basis for further functional characterization of WRKY genes with the intention of improving T. sinensis.